2021
DOI: 10.1111/ejn.15150
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble epoxide hydrolase (sEH) protects hippocampal neurons and reduces cognitive decline in type 2 diabetic mice

Abstract: Diabetes mellitus is a metabolic disorder that can lead to cognitive dysfunction. The hippocampus plays an important role in the cognitive function. Research has identified correlations between hippocampal impairment and diabetes, yet their intermediate remains unclear. Soluble epoxide hydrolase (sEH) is an enzyme that degrades epoxyeicosatrienoic acids (EETs), which have multiple protective effects by suppressing inflammation, apoptosis and oxidative stress. In this study, under diabetic conditions both hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Additionally, cardiometabolic disorders and cognition share circulating biomarkers and risk factors 6 . Our primary hypothesis was that cognitive decline is associated with an abrogation of normal epoxy fatty acid status based on findings that inhibition of soluble epoxide hydrolase, an enzyme previously implicated in the regulation of microvascular tone and inflammation, protects hippocampal neuronal death and reduces cognitive decline in mice 7 , and that genetic deletion of this enzyme slows amyloid beta associated Alzheimer’s disease onset in mice 8 . Further studies have shown that sEH inhibition reduces neuroinflammation 9 and alpha-synuclein aggregation 10 , 11 , pathological feature of multiple neurocognitive disorders 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cardiometabolic disorders and cognition share circulating biomarkers and risk factors 6 . Our primary hypothesis was that cognitive decline is associated with an abrogation of normal epoxy fatty acid status based on findings that inhibition of soluble epoxide hydrolase, an enzyme previously implicated in the regulation of microvascular tone and inflammation, protects hippocampal neuronal death and reduces cognitive decline in mice 7 , and that genetic deletion of this enzyme slows amyloid beta associated Alzheimer’s disease onset in mice 8 . Further studies have shown that sEH inhibition reduces neuroinflammation 9 and alpha-synuclein aggregation 10 , 11 , pathological feature of multiple neurocognitive disorders 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical role of sEHIs has been reviewed [22]. In clinical trials, sEHIs play a protective role in hypertension [94], and in animal models, they demonstrate neuroprotection in stroke [27,28], cerebral hypoperfusion, and in diabetes type 1 and type 2 [29][30][31][32][33]. Our studies show that sEHIs may also be promising therapeutic targets in the microvascular endothelial dysfunction that accompanies Alzheimer's and vascular dementias.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 73%
“…A HGD is a risk factor for dementia [14] and is associated with poor cognitive performance [15,16], but whether the effect can be reversed has also been unknown. Given that in murine models of diabetes, soluble epoxide hydrolase inhibitors (sEHI) reduce neuroinflammation and cognitive decline [32][33][34], we also aimed to examine their role in our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotoxins such as Aβ, epoxide hydrolase (sEH), dichloroacetic acid, paroxetine, NO, and doxorubicin increase the FR concentration, which is responsible for ROS-induced neuronal cell death and ultimately leads to cognitive impairment and synaptic dysfunction. Administration of neurotoxins disrupts the mitochondrial membrane permeability and alters the calcium homeostasis (Toledo et al 2021;Sheikholeslami et al 2021;Wang et al 2021;Wu et al 2021;Wei et al 2021). To reverse the effects of neurotoxin-induced oxidative stress, the efficacy of antioxidant properties has been tested in both in vivo and in vitro conditions.…”
Section: Synaptic Dysfunction and Synaptic Plasticitymentioning
confidence: 99%